Outcomes research shifting the dominant research paradigm in physical therapy - Alan M. Jette (AOSIS, 1997)
This article discusses outcomes research in physical therapy and places its conceptual roots within the work on quality-of-care assessment. An argument is advanced that the outcomes research movement in medicine has stimulated clinical researchers in physical therapy to address disability outcomes in addition to traditional impairment outcomes. If physical therapy clinical research moves beyond this broadening of clinical outcomes to investigate explicitly the hypothesized relationship between impairment and disability, outcomes research will have stimulated a shift in the dominant research paradigm in the profession. The development and testing of theory regarding the pathogenesis of disability will be needed to guide the direction of this type of physical therapy research. Such a shift in the dominant research paradigm in physical therapy could produce dramatic findings that have direct impact on clinical practice.